Subacute Sclerosing Panencephalitis (SSPE) in Toddlers and Young Children: A Case Series (Bangladesh Journal of Child Health, 2020)
SSPE is a neurodegenerative disorder caused by persistent defective or mutant measles virus. The disease has a gradual progressive course leading to death within 1-3 yrs or even early. SSPE is a disease of childhood and early adolescence. The classic age at presentation is 8-11 years and usually occurs after a latent period of average 6 years. Here we report 3 cases of SSPE in toddlers. Diagnosis was made on the basis of clinical presentation, EEG pattern and elevated CSF anti measles antibody titer as described in Dykan criteria for diagnosis of SSPE. Clinical presentation was very early with a relatively shorter latency and fatal progression. Two patients had past history of measles and all patients were immunized against measles. One patient died within 4 months of disease expression and 2 patients went into vegetative state within 3 months of disease onset.Bangladesh J Child Health 2020; VOL 44 (2) :114-117